Tata letak From to Chart (FTC), Activity Relationship Chart (ARC), Activity Relationship Diagram (ARD), dan Area Allocation Diagram (ADD). - Prasetyani Rini Rini Prasetyani (Fakultas Sains Dan Teknologi, 2023)
Waste management in Tegal Regency is using an open dumping system. Open dumping waste treatment system is the worst waste management system, because in principle this system is disposing of garbage, stockpiled with soil obtained from the hills in the landfill, and there is no follow up from the waste. So we need a waste management system with the concept of zero waste. A waste management system with the concept of zero waste is a waste management system that does not produce waste again when the output of the processing results. The concept will later be developed into PLTSa in Tegal Regency. The making of PLTSa will certainly require a large enough area to have enough supporting areas to run the process of PLTSa. Later Penujah PLTSa area will not only be designated as a power plant but will also be developed into an educational tourism area. Making PLTSa will certainly require a large enough area to have enough supporting areas for the process of PLTSa to run. This mini plant area was designed using the From to Chart (FTC) method, Activity Relationship Chart (ARC), Activity Relationship Diagram (ARD), and Area Allocation Diagram (ADD). The results of the design produce the type of production layout that is Group Technology Layout and alternative layout 1 as a proposed layout.